Estudo ecológico e patológico de comunidades parasitárias infestando tilápia-do-Nilo criadas em tanques-rede - Pala, Gabriela [UNESP] (2016)
This review describes how the parasite ecology, epidemiology and pathology enables the development of effective strategies for ictiossanitário control in the intensive fish creations. The Nile tilapia (Oreochromis niloticus) is one of the species most created in the world, with growth of 105% in seven years in Brazil, producing more than 700,000 tonnes per year, corresponding to 26% of the national aquaculture production. Due to the current aquaculture expansion, there was intensification of production, increasing animal stocking density, which predisposes to the appearance of parasitic and bacterial diseases. Parasites of fish cause significant losses in fish farming worldwide, causing often irreversible damage that facilitate the installation of opportunistic bacterial infections that lead the host to death. Tilapia can be parasitized by several species of ciliated protozoa, flagellate protozoa, myxosporean, Monogenoidea, various genres of digenetic and cestóideos, Acanthocephala, for various kinds of nematóideos and crustaceans. Therefore, there is the need to develop studies on parasite ecology area, accumulating new data to the control of fish diseases. Research in taxonomy area are important for the diagnosis of parasitic diseases, which are scarce in fish farming, as well as ecological descriptions, epidemiological, biological, pathological and parasite / host relationship